Immune regulation effect of lienal polypeptides extract in Lewis lung carcinoma-bearing mice treated with cyclophosphamide. Issue 1 (January 2018) - Wu, Yan-Ping; Deng, Jie; Ouyang, Shu-Hua; Mao, Zhong-Fu; Wang, Guo-En; Kurihara, Hiroshi; He, Rong-Rong; Li, Yi-Fang
Polypeptides extracted from animal immune organs have been proved to exert immunomodulatory activities in previous reports. However, relative experimental data regarding the influence of a polypeptide mixture extracted from healthy calf spleen (lienal polypeptide [LP]) on the immune function in tumor therapy are limited, and the components in LP remain unclear. In the present study, the immune regulatory effect of LP was investigated in normal mice and Lewis lung carcinoma (LLC)-bearing mice treated with cyclophosphamide (CTX). The components of LP were identified by liquid chromatography–electrospray ionization-coupled with tandem mass spectrometry (LC–MS/MS) analysis and bioinformatic analysis. In LLC-bearing mice, LP showed a synergic antitumor effect with CTX, whereas LP alone did not present direct antitumor activity. Further, LP was found to enhance immune organ indexes, splenocyte number, and T lymphocyte subsets in normal mice and LLC-bearing mice treated with CTX. The decline of white blood cell and platelet counts, splenocyte proliferation activity, and peritoneal macrophage phagocytic function caused by CTX were also significantly suppressed by LP treatment in LLC-bearing mice. Notably, LP treatment significantly decreased the expression of phagocytosis-related proteins including CD47/signal regulatory protein α/Src homology phosphatase-1 in the tumor tissue of LLC-bearing mice treated with CTX. LC-MS/MS-based peptidomics unraveled the main polypeptides in LP with a length from 8 to 25 amino acids. Bioinformatics analysis further confirmed the possibility of LP to regulate immunity, especially in phagocytosis-related pathway. Our above findings indicated that LP can relieve the immunosuppression induced by chemotherapy and is a beneficial supplement in cancer therapy. Impact statement: The immunomodulatory activities of polypeptides extracted from animal immune organs have incurred people's interests since a long time ago. In this study, we investigated the immune regulation effects of a polypeptide mixture extracted from health calf spleen (lienal polypeptide [LP]) in Lewis lung carcinoma-bearing mice treated with cyclophosphamide (CTX). Liquid chromatography–electrospray ionization-coupled with tandem mass spectrometry-based peptidomics and bioinformatics analysis unraveled the main polypeptides in LP and further confirmed that LP is mainly associated with immune regulating pathway, especially in tumor cell phagocytosis-related pathway. Our study for the first time revealed that polypeptides from spleen can relieve the immunosuppression induced by CTX and is a beneficial supplement in cancer therapy.